Scaffold vascularization method using an adipose-derived stem cell (ASC)-seeded scaffold prefabricated with a flow-through pedicle - Dębski, Tomasz (Stem Cell Res Ther, 2020)
BACKGROUND: Vascularization is important for the clinical application of tissue engineered products. Both adipose-derived stem cells (ASCs) and surgical prefabrication can be used to induce angiogenesis in scaffolds. Our aim was to compare the angiogenic potential of ASC-seeded scaffolds combined with scaffold prefabrication with that of non-seeded, non-prefabricated scaffolds. METHODS: For prefabrication, functional blood vessels were introduced into the scaffold using a flow-through pedicle system. ASCs were isolated from rat fat deposits. Three-dimensional-printed cylindrical poly-ε-caprolactone scaffolds were fabricated by fused deposition modelling. Three groups, each containing six rats, were investigated by using non-seeded, ASC-seeded, and osteogenic induced ASC-seeded scaffolds. In each group, one rat was implanted with two scaffolds in the inguinal region. On the right side, a scaffold was implanted subcutaneously around the inferior epigastric vessels (classic prefabrication group). On the left side, the inferior epigastric vessels were placed inside the prefabricated scaffold in the flow-through pedicle system (flow-through prefabrication group). The vessel density and vascular architecture were examined histopathologically and by μCT imaging, respectively, at 2 months after implantation. RESULTS: The mean vessel densities were 10- and 5-fold higher in the ASC-seeded and osteogenic induced ASC-seeded scaffolds with flow-through prefabrication, respectively, than in the non-seeded classic prefabricated group (p < 0.001). μCT imaging revealed functional vessels within the scaffold. CONCLUSION: ASC-seeded scaffolds with prefabrication showed significantly improved scaffold vasculogenesis and could be useful for application to tissue engineering products in the clinical settings.